The Influence of Work-Life Balance and Workload on Employee Job Satisfaction at the Samsat UPT Regional Revenue Office Makassar I Selatan - imam, imamsatriaalam; Natsir, Uhud Darmawan; Ruma, Zainal; Haeruddin, M. Ilham Wardhana; Hamka, Rezky Amalia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to determine the influence of work life balance and workload on employee job satisfaction at the SAMSAT UPT Revenue Office, South Makassar I Region. This research employed a quantitative associative approach with a survey technique. The population of this study consisted of all 80 employees at the e SAMSAT UPT Revenue Office, South Makassar I Region, and the entire population was selected as the sample using saturated sampling. Data were collected through questionnaires and analyzed using multiple linear regression method with the aid of SPSS version 26 application. The results indicate that work life balance has a positive and significant effect on employee job satisfaction, while workload has a negative and significant effect on job satisfaction. Simultaneously, work life balance and workload significantly influence job satisfaction. The coefficient of determination (R²) value shows that work life balance and workload contribute 28.3% to employee job satisfaction.